Life cycle analysis of thermosyphon solar water heaters - Kalogirou, Soteris A. (My University, 2008)
In this paper, a life cycle analysis of thermosyphon solar water heating systems is presented. This includes the performance, economics and environmental benefits offered by the system investigated which is of the domestic size, suitable to satisfy most of the hot water needs of a four-person family. The results presented in this paper show that the solar contribution is 79%, the pay back time is 2.4 years and life cycle savings are €3014 with electricity backup and 3.1 years and €2010 with diesel backup respectively. Additionally, by using solar energy considerable amounts of greenhouse polluting gasses are avoided. The energy spent for the manufacture and installation of the solar systems is recouped in about 13 months. It can therefore be concluded that thermosyphon solar water hearting systems offer significant protection to the environment and should be employed whenever possible in order to achieve a sustainable future.
Keywords: Thermal performance; Economic analysis; Life cycle analysis; Thermosyphon solar water heaters